Impact of frequent cerebrospinal fluid sampling on Aβ levels: systematic approach to elucidate influencing factors. Issue 1 (December 2016) - Van Broeck, Bianca; Timmers, Maarten; Ramael, Steven; Bogert, Jennifer; Shaw, Leslie; Mercken, Marc; Slemmon, John; Van Nueten, Luc; Engelborghs, Sebastiaan; Streffer, Johannes
Abstract Background Cerebrospinal fluid (CSF) amyloid-beta (Aβ) peptides are predictive biomarkers for Alzheimer's disease and are proposed as pharmacodynamic markers for amyloid-lowering therapies. However, frequent sampling results in fluctuating CSF Aβ levels that have a tendency to increase compared with baseline. The impact of sampling frequency, volume, catheterization procedure, and ibuprofen pretreatment on CSF Aβ levels using continuous sampling over 36 h was assessed. Methods In this open-label biomarker study, healthy participants (n = 18; either sex, age 55 − 85 years) were randomized into one of three cohorts (n = 6/cohort; high-frequency sampling). In all cohorts except cohort 2 (sampling started 6 h post catheterization), sampling through lumbar catheterization started immediately post catheterization. Cohort 3 received ibuprofen (800 mg) before catheterization. Following interim data review, an additional cohort 4 (n = 6) with an optimized sampling scheme (low-frequency and lower volume) was included. CSF Aβ1–37, Aβ1–38, Aβ1–40, and Aβ1–42 levels were analyzed. Results Increases and fluctuations in mean CSF Aβ levels occurred in cohorts 1–3 at times of high-frequency sampling. Some outliers were observed (cohorts 2 and 3) with an extreme pronunciation of this effect. Cohort 4 demonstrated minimal fluctuation of CSF Aβ both on a group and an individual level. Intersubject variability in CSF Aβ profiles over time was observed in all cohorts. Conclusions CSF Aβ level fluctuation upon catheterization primarily depends on the sampling frequency and volume, but not on the catheterization procedure or inflammatory reaction. An optimized low-frequency sampling protocol minimizes or eliminates fluctuation of CSF Aβ levels, which will improve the capability of accurately measuring the pharmacodynamic read-out for amyloid-lowering therapies. Trial registration ClinicalTrials.govNCT01436188 . Registered 15 September 2011.